A New Oxaliplatin Resistance-Related Gene Signature With Strong Predicting Ability in Colon Cancer Identified by Comprehensive Profiling - Lin, Qiu; Luo, Li; Wang, Hua (Frontiers in Oncology, 2021)
Numerous colon cancer cases are resistant to chemotherapy based on oxaliplatin and suffer from relapse. A number of survival- and prognosis-related biomarkers have been identified based on database mining for patients who develop drug resistance, but the single individual gene biomarker can not attain high specificity and sensitiv-ity in prognosis predictionh. This work was conducted aiming to establish a new gene signature using oxaliplatin resistance-related genes to predict the prognosis for colon cancer. To this end, we downloaded gene expression profile data of cell lines resistant and not resistant to oxaliplatin from the Gene Expression Omnibus (GEO) database. Altogether 495 oxaliplatin resistance-related genes were searched by weighted gene co-expression network analysis (WGCNA) and differential expression analysis. As suggested by functional analysis, the above genes were mostly enriched into cell adhesion and immune processes. Besides, a signature was built based on 4 oxaliplatin resistance-related genes selected from training set to predict the overall survival (OS) by stepwise regression and least absolute shrinkage and selection op-erator (LASSO) Cox analysis. Relative to low risk score group, the high risk score group had dismal OS (P <0.0001). Moreover, the area under the curve (AUC) value regarding the 5-year OS was 0.72, indicating that the risk score was accurate in the prediction of OS for colon cancer patients (AUC > 0.7). Additionally, multivariate Cox regression suggested that, the signature constructed based on 4 oxaliplatin re-sistance-related genes predicted the prognosis for colon cancer cases (HR, 2.77; 95% CI, 2.03–3.78; P<0.001). Finally, external test sets were utilized to further validate the stability and accuracy of oxaliplatin resistance-related gene signature for prog-nosis of colon cancer patients. To sum up, this study establishes a signature based on 4 oxaliplatin resistance-related genes for predicting the survival of colon cancer pa-tients, which sheds more lights on the mechanisms of oxaliplatin resistance and helps to identify colon cancer cases with dismal prognostic outcome.